2003
DOI: 10.1097/01.brs.0000048655.43106.08
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cervical Spine Trauma Showing Symptomatic Calcified Cervical Disc Herniation in a Child

Abstract: In the presence of a large, calcified cervical disc herniation, mild cervical trauma may result in the onset of severe spastic myelopathy warranting surgical correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…2 CT scan is also valuable for confirming the presence of calcification in the herniated disc. 5 In the current study, the CT scan demonstrated a central calcification in the C3-C4 intervertebral space, as well as a herniated calcification into the C3 foramen transversarium (Figure 3). The two calcified zones were separate, because we did not find a complete bridging between the two zones when viewing all the CT Figure 3.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…2 CT scan is also valuable for confirming the presence of calcification in the herniated disc. 5 In the current study, the CT scan demonstrated a central calcification in the C3-C4 intervertebral space, as well as a herniated calcification into the C3 foramen transversarium (Figure 3). The two calcified zones were separate, because we did not find a complete bridging between the two zones when viewing all the CT Figure 3.…”
Section: Discussionmentioning
confidence: 90%
“…1,4,8 Operative treatment is reserved for the very rare patients presenting with severe radicular pain or with progressive neurologic deficit resulting from nerve root or spinal cord compression. 4,5,11 This unusual case also suggests that in the clinical evaluation of a patient with JIDC of the cervical spine, one has to seek evidence of vertebral artery insufficiency in addition to the signs of root or spinal cord compression. Symptoms such as headache, syncope, vertigo, tinnitus, ataxia, dysarthria, visual disturbance, Horner's syndrome, vomiting, or dysphagia should alert the physician about the possibility of vertebral artery insufficiency resulting from herniation of the calcified disc into the foramen transversarium.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In rare cases of spinal cord and/or nerve Figure 2 Preoperative T2-weighted sagittal magnetic resonance image demonstrating a large extradural mass, of very low signal intensity into the spinal canal at the C7/Th1 level, causing a severe compression on the dural sac and spinal cord posteriorly Figure 1 A plane radiograph of the lateral spine demonstrating lack of apparent calcification at disc level root compression by herniation of the calcified disc, it has been reported that operative removal of the disc is indicated. 4,5,8,11,12 Anterior cervical discectomy with or without fusion has been reported in the literature only in a few cases. 4,5,7,8,[11][12][13] All patients became asymptomatic after the displaced disc lesion was removed.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8,11,12 Anterior cervical discectomy with or without fusion has been reported in the literature only in a few cases. 4,5,7,8,[11][12][13] All patients became asymptomatic after the displaced disc lesion was removed. Peck 14 and MacCartee 15 have reported cases of thoracic calcified nucleus pulposus that had ruptured into the spinal canal, causing signs of cord compression, relieved by laminectomy.…”
Section: Discussionmentioning
confidence: 99%